(untitled) (Jurnal Geomine, 2021)
The Bobong Formation is one of the rock formations on Taliabu Island which contains Jurassic coal seams. This study aims to analyze the organic petrographic and geochemical characteristics of coal in the study area. The method used includes field observations and coal sampling which is done by ply by ply channel sampling method. Laboratory analysis conducted on 10 coal samples included organic, proximate, ultimate and gross calorific value (calorific value) analysis. The Bobong Formation coal consists of 3 seams, including seam 1 with a thickness of 0.5 m to 1 meter, seam 2 that is 1 meter in thick, and seam 3 with the thickness of 0.50 m to 0.90 meters. The three coal seams are predominantly classified in the bright coals and banded bright coals lithotype. The coal has a gross calorific value of 13,896.26-15,362.54 (Btu / lb) and a proximate value in the form of tethered carbon 36.10 - 43.86 (%, adb), flight substance content 38.25 - 47.91 (%, adb ), water content from 6.54 - 12.23 (%, adb) and ash content from 64.46 - 21.31 (%, adb). Coal seam 1, seam 2 and seam 3 are included in high volatile A bituminous coals. Ultimat in the Bobong Formation coal is carbon 64.46 - 74.75 (%, daf), hydrogen 6.27 - 6.92 (%, daf), nitrogen 0.76 - 0.87 (%, daf), sulfur 4 , 41 - 7.93 (%, adb) and oxygen 9.45 - 18.07 (%, daf). Meanwhile, the maceral values in the form of vitrinite are 69.75 - 77.52 (%, vol), liptinite 17.56 - 22.50 (%, vol) and inertinite 3.60 - 7.75 (%, vol).